Retorika Dakwah di kelurahan Tassililu kec. Sinjai Barat Dalam Mencegah Radikalisme - Musliadi Musliadi; R. Firdaus Wahyudi (Fakultas Ushuluddin dan Komunikasi Islam, 2023)
Da'wah rhetoric is the art of conveying da'wah messages, this art aims so that the messages conveyed by the preacher can be well received by listeners in an effort to prevent radicalism in Tassililu village, especially to youth or mosque youth, da'wah rhetoric training activities are certainly an alternative that can be done so that young people or young people in the mosque can understand and accept sentences or da'wah messages conveyed by a da'i so that later when they grow up they can distinguish between sentences that can lead to actions that contain elements of radicalism. The method used Delivery of material and discussion and practice. The attitude of the youth of the mosque when carrying out preaching practices, the smooth process of communication in preaching, is a method used by humans in an effort to share meaning through the transmission of symbolic messages which is very important.